DIPG-11. NEURAL PRECURSOR CELL:GLIOMA INTERACTIONS MEDIATE TUMOR COLONIZATION OF THE SUBVENTRICULAR ZONE BY DIPG. (31st May 2017) - Qin, Elizabeth Y.; Cooper, Dominique; Abbott, Keene; MacKay, Alan; Jones, Chris; Vogel, Hannes; Jackson, Peter; Monje, Michelle
Abstract: The lateral ventricle subventricular zone (SVZ) stem cell niche is thought to be a sanctuary site for high-grade gliomas, and is thus critical for tumor survival and recurrence. This is true for both adult glioblastoma and pediatric high-grade gliomas such as diffuse intrinsic pontine glioma (DIPG). In DIPG, a devastating childhood brain cancer characterized by its diffusely infiltrating nature, the SVZ is not only an anatomical site of frequent spread, but also a site of clinically significant growth. We have sought to understand how and why DIPG and other high-grade gliomas spread so frequently to the SVZ, and hypothesized that this predilection is mediated by interactions between the glioma cells and the neural precursor cells that normally reside in the SVZ. Our present studies support this hypothesis of neural precursor cell:glioma cell communication, showing that SVZ neural precursor cells secrete chemoattractant signals toward which DIPG cells home. Biochemical and proteomic studies on factors secreted by SVZ neural precursor cells reveal a discrete list of candidate proteins. Necessity and sufficiency testing implicate the neurite outgrowth-promoting factor pleiotrophin, along with three binding partners (secreted protein acidic and rich in cysteine (SPARC), SPARC-like protein 1, and heat shock protein 90B), as key mediators of this chemoattractant effect. Ongoing studies further investigating the molecular pathways involved seek to expand on these observations to identify potentially targetable mechanisms for high-grade glioma therapy.